Exploration of the active components and mechanisms of Epimedium for the treatment of Undescended Testis - Deng, Zhonglei; Zhang, Sirui; Zhao, Haiyang; Xu, Shijia; Qi, Miao; Pu, Tianle; Wang, Hui (Frontiers in Endocrinology, 2025)
BackgroundUndescended Testis, the most common congenital male reproductive disorder in children, demonstrates complex pathogenesis with genetic predisposition. While early surgical intervention (before 18 months) remains standard care, pharmacological options are limited.PurposeExplore the therapeutic potential of Traditional Chinese Medicine for Undescended Testis.Study designThis study employs multiple bioinformatics approaches to search for potential Traditional Chinese Medicines for Undescended Testis treatment and investigate their therapeutic mechanisms.MethodsThis study integrated medication regularity analysis, network pharmacology, Mendelian randomization, and molecular docking, with exploration conducted through cellular and animal models.ResultsOur analysis identified 27 bioactive Epimedium compounds, with Quercetin, Kaempferol, and Icariin showing particular promise. Protein interaction networks revealed AKT1, PARP1, and PGR as key targets. Functional enrichment analysis primarily focused on biological processes including response to stress-induced damage (such as reactive oxygen species, chemical toxins, and other stressors), steroid signaling and receptor activation, transmembrane signal transduction, as well as cellular proliferation and apoptosis regulation. Molecular docking demonstrated Yinyanghuo B’s strong binding affinity with PARP1 (-7.2 kcal/mol). Mendelian randomization confirmed PARP1 reduction’s causal relationship with lower Undescended Testis risk. We constructed animal and cellular heat stress models to simulate Undescended Testis, and subsequent experiments observed significant DNA damage. Thermally stressed TM4 cells showed significant PARP1 upregulation, suggesting its critical role in testicular heat stress response by accelerating DNA damage repair.ConclusionThese findings potentially provide mechanistic evidence supporting Epimedium’s traditional use while advancing Traditional Chinese Medicine modernization through contemporary pharmacological validation.